Pemetaan Plasma Nutfah dan Kualitas Ekspor Buah Vanili pada Koperasi Petani Vanili Karavan Donohudan Boyolali - Mudyantini, Widya; Suranto, Suranto; Solichatun, Solichatun; Pitoyo, Ari; Suratman, Suratman; Purnama, Purin Candra (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2025)
Membership of the Indonesian Vanilla Spice producer cooperative "KARAVAN" with a Secretariat office in Donohudan-Surakarta, consisting of 18 districts/cities including Semarang, Ungaran, Kudus, Pati, Grobogan, Blora, Salatiga, Temanggung, Magelang, Kendal, Pekalongan, Karanganyar, Wonogiri , Tegal, Surakarta, Purwokerto, Banyumas, Purworejo, Kulonprogo (DIY). The number of members of the 126 farmer cooperative is around 1300 farmers. The production capacity of assisted vanilla farmers for green reaches 7-8.5 tons of green with a distribution on the Muria slope of around 1-1.5 tons. Salatiga, Ambarawa, Temanggung 2 tons. Wonosobo, Pekalongan, Kendal to Tegal around 3-4 tons, Magelang Purworejo, Banyumas around 2.5-3.5 tons per year. Some potential buyer countries include Switzerland, Germany, Malaysia, the Netherlands and Taiwan. One of the requirements for export is proof of vanillin content testing from a laboratory that has been accredited by KAN, including the UNS Integrated Laboratory UPT. Funding assistance for vanillin level testing is very necessary for farmers. This service helps with the costs of testing vanillin levels at different locations and finding optimal post-harvest handling standards for all members so that the results of vanillin levels can be uniform. Activities that have been carried out include holding an FGD between Karavan farmer cooperative partners and the UNS Integrated Laboratory UPT, BSN (National Standardization Agency) and the Plant Biomaterials Research Group on Wednesday, June 12 2024. This activity aims to make the vanilla farmer cooperative a BSN foster partner in assisting with SNI registration. Also making service partners the main clients in testing vanillin levels at the UNS Integrated Laboratory UPT. Various issues regarding germplasm, cultivation and post-harvest are assisted by the Plant Biomaterials Research Group. This service also involved taking part in an exhibition for the 48th Anniversary in front of the Rectorate on Friday – Saturday 21-22 June 2024. To train and apply the technology for drying vanilla fruit in an oven, research was carried out based on existing journals on vanilla fruit. The best treatment for drying and heating treatment is a water temperature of 55 oC and an oven of 40 oC ( on September 19). The vanillin content test was carried out and the levels were measured in 9 samples from 7 regions. From Tegal (Guci area) the vanillin levels were 1.70%, 1.78% and 1.73% with a standard deviation of 0.04%, the three samples were not significantly different. From Kudus (Mount Muria) 1.86%, Grobogan Sukolilo (North Gendeng) 1.54%, Lumajang (Bromo) 1.20%, Ambarawa 1.46%, Pati 1.59%, Magelang (Gunung Kelir-Ngablak) 1, 52%. The highest levels were from Kudus, followed by Tegal, Pati, Grobogan, Magelang, Ambarawa, and the lowest was Lumajang. Kata kunci :  Vanillin levels, germplasm, exports, Karavan vanilla farmers' cooperative